Deep Neural Networks in Medical Image Classification - Skobel, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents two approaches to the problem of classifying cytological images. The first approach is based on the extraction of deep features resulting from training the network to correctly classify a set of cytological and histopathological images. The second approach starts with semantic segmentation of objects in the image. A diverse set of features is then created based on the segmented cell nuclei. Extraction, which belongs to dimensionality reduction methods, is one of the basic approaches to building a set of features.
Keywords: diagnostyka obrazowa; rak piersi; sztuczne sieci neuronowe (SSN); Polska; raport z badań; rozprawa doktorska